Correlation between Office Locations, Corporate Governance and Business Performance - Lin, Shih-Yao; Hsui, Ai-Chi (International Journal of Economics and Financial Issues, 2017)
The concept of “corporate governance” developed in an era marked by global economic liberalization, continuing enterprise expansion, and separation enterprise ownership and management trends. Good corporate governance is important to enhance corporate value and national competitiveness. “Locations” refer to spaces wherein human social activities are held. Office activities have become important economic human activities, and enterprise headquarters are the primary places where enterprises issue orders, carry out corporate control, and make decisions. Hence, they are vital to the overall operation of enterprises. Do the locations of enterprise headquarters influence corporate governance quality, and thus, the overall business performance of enterprises? This research analyzes Taiwan's listed and over-the-counter companies. As per empirical results: (1) Corporate business performance significantly correlates with corporate governance and office locations, with a significant difference between various areas, and (2) the quality of corporate governance of Taiwanese enterprises significantly correlates and varies with their office locations. Keywords: Corporate Governance, Business Performance, Location Theory JEL Classifications: G34, M10, R39